Manifestations Of Fear Of Heights In Military Personnel In Extreme Situations - Adiljanovna, Ahmadjonova Nargizaxon; qizi, Yulchiyeva Shoxsanam Dilshod (Indonesian Journal Publisher, 2025)
This article describes a ten-day study of the manifestation of aspects of fear of heights among students of military educational institutions in difficult and extreme situations. The manifestation of fear of heights was studied, on the basis of which step-by-step recommendations for motivation are given overcoming fear of heights. During the ten-day program, each subject's pulse, saturation and pressure at critical points of manifestation of fear of heights. For clarity, the results of studies of military subjects under a ten-day program with a safety rope tabulated. After applying the ten-day program (10 types different from each other types of descent) from the height of a five-story building, the subjects' fear of heights was transformed into a unique type of load, allowing them to eliminate the accumulated stress from other stressful circumstances.